2022
DOI: 10.1038/s41423-022-00929-3
|View full text |Cite
|
Sign up to set email alerts
|

A triple-RBD-based mucosal vaccine provides broad protection against SARS-CoV-2 variants of concern

Abstract: The rapid mutation and spread of SARS-CoV-2 variants urge the development of effective mucosal vaccines to provide broad-spectrum protection against the initial infection and thereby curb the transmission potential. Here, we designed a chimeric triple-RBD immunogen, 3Ro-NC, harboring one Delta RBD and two Omicron RBDs within a novel protein scaffold. 3Ro-NC elicits potent and broad RBD-specific neutralizing immunity against SARS-CoV-2 variants of concern. Notably, intranasal immunization with 3Ro-NC plus the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…2e ). 26 , 28 Consistent with the defective of the TLR5 agonist, intranasal immunization of 4 µg 3R-NC without mucosal adjuvant could hardly induce RBD-specific serum IgG and salivary IgA (Fig. 1e ).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…2e ). 26 , 28 Consistent with the defective of the TLR5 agonist, intranasal immunization of 4 µg 3R-NC without mucosal adjuvant could hardly induce RBD-specific serum IgG and salivary IgA (Fig. 1e ).…”
Section: Resultssupporting
confidence: 63%
“…In this study, we employed a highly stable triple-RBD scaffold protein platform capable of accommodating various combinations of three RBDs. 26 Two novel triple-RBD scaffold proteins, namely 3R-NC and 3R AEW -NC, were designed as immunogens for SARS-CoV-2 mucosal vaccines to address the persistent challenge of frequently emerging variants. Nasal vaccination of 3R-NC with an optimized flagellin adjuvant KFD ( 3R-NC + KFDi.n ), triggered high-level, long-lasting, and broad cross-reactive RBD-specific neutralizing antibodies, in both serum and mucosal sites.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the administration of a mucosal vaccine in addition to the approved intramuscular protocol could provide the sterilizing immunity required to efficiently block viral circulation and the emergence of new VOC efficiently. 48 , 49 …”
Section: Discussionmentioning
confidence: 99%
“… 7 Recently, an inhaled COVID vaccine named Convidecia Air has been approved for emergency use as a booster in China. 8 We have designed a bivalent chimeric triple-RBD immunogen containing one Delta RBD and two Omicron RBDs (3Ro-NC) 9 (Supplementary Fig. 1 ) and demonstrated that intranasal (i.n) immunization with 3Ro-NC plus recombinant flagellin KFD adjuvant could induce robust systemic and mucosal immunity against SARR-CoV-2 VOCs.…”
mentioning
confidence: 99%